2021
DOI: 10.3390/s21144659
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Camera Vessel-Speed Enforcement by Enhancing Detection and Re-Identification Techniques

Abstract: This paper presents a camera-based vessel-speed enforcement system based on two cameras. The proposed system detects and tracks vessels per camera view and employs a re-identification (re-ID) function for linking vessels between the two cameras based on multiple bounding-box images per vessel. Newly detected vessels in one camera (query) are compared to the gallery set of all vessels detected by the other camera. To train and evaluate the proposed detection and re-ID system, a new Vessel-reID dataset is introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Zwemer et al [15] proposed a system that uses two cameras to estimate the velocity of ships. In addition, the proposed system detects and tracks ships through re-identification (re-ID) tasks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Zwemer et al [15] proposed a system that uses two cameras to estimate the velocity of ships. In addition, the proposed system detects and tracks ships through re-identification (re-ID) tasks.…”
Section: Related Workmentioning
confidence: 99%
“…The authors, like Zwemer et al [15], have identified that incorrect detections frequently occur due to unfavorable lighting conditions. In addition, since some evaluated scenarios come from cameras with less color saturation, the background subtraction algorithm performs worse in these scenarios.…”
Section: Related Workmentioning
confidence: 99%